Fungsi Lembaga Riset sebagai Referensi Elektabilitas Politik Studi Data Hasil PEMILU 2019 di DAPIL II Jawa Barat DPR-RI dan Lembaga Survei Yayasan Polsight Indonesia - Salwa Nazhira (Talenta Publisher, 2024)
Research institutions in Indonesia are currently mushrooming according to the needs of many developing sectors, one of which is the political sector in which there are many dynamics that can be calculated and calculated with numbers or not. For things that can be calculated, research institutions can be used as a method to find out political dynamics and phenomena, where this can be used as a reference and prediction regarding a political situation in the future, one of which is in terms of measuring political electability by either an individual or an institution. In this case, research institutions have a very important role in producing information about political electability accompanied by data and facts that occur in the field so that it can be said that research institutions can provide objective and factual references. One of the data that can be used as a reference for electability is voter data from a candidate or political party in an electoral district.